PENGARUH KECEMASAN MENGHADAPI PEMUTUSAN HUBUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA PT MUJUR TIMBER SIBOLGA - Melsa Siagian; Muhammad Yafiz (ITB AAS Indonesia Surakarta, 2023)
The purpose of this research is to find out how the influence of anxiety facing termination of employment on the work motivation of employees at PT Mujur Timber Sibolga. This study involved 71 employees of PT Mujur Timber Sibolga who were still actively working at PT Mujur Timber Sibolga to become respondents or samples. the data collection uses a psychological scale, namely the work motivation scale and the anxiety scale. The data used is primary data which was analyzed by simple linear regression test using SPSS version 25. Then the results obtained from the study are the correlation value between the work anxiety variable and the work motivation variable of 0.698, so it can be concluded that there is a strong relationship between the variables work anxiety with work motivation variables. In this study it was found that the coefficient of determination or R-square was 0.487 or 48.7%, so the researchers stated that the work motivation variable was influenced by 48.7% of the work anxiety variable, and for the other 51.3% it was influenced by other variables. Keywords : Anxiety, Employees, Work motivation